2018
DOI: 10.1002/elan.201700716
|View full text |Cite
|
Sign up to set email alerts
|

Robust, Bridge‐less Ion‐selective Electrodes with Significantly Reduced Need for Pre‐ and Post‐application Handling

Abstract: We are demonstrating robust, single‐layer ion‐selective electrode (ISE) utilizing simple Ag/AgCl electrode as solid support without the need for intermediate polymer layer. We have created and chemically linked a family of imidazolium ionic liquids (ILs) with poly (vinyl chloride) (PVC) using click chemistry, resulting in hybrid materials with tunable characteristics. The resultant material inherently contains chloride ion thus offering the ability to stabilize interfacial potential. This allowed us to constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Deviations of the observed selectivity coefficients from the well-known Hofmeister series were found, suggesting binding functionalities of the IL . Schazmann et al reported on a solid-contact anion-SE based on the family of imidazolium salts covalently linked to PVC . Here, the IL, with chloride as a counterion, served as an anion exchanger and a salt bridge, stabilizing the interfacial potential between the Ag/AgCl electrode substrate and the membrane.…”
Section: Sensor Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deviations of the observed selectivity coefficients from the well-known Hofmeister series were found, suggesting binding functionalities of the IL . Schazmann et al reported on a solid-contact anion-SE based on the family of imidazolium salts covalently linked to PVC . Here, the IL, with chloride as a counterion, served as an anion exchanger and a salt bridge, stabilizing the interfacial potential between the Ag/AgCl electrode substrate and the membrane.…”
Section: Sensor Materialsmentioning
confidence: 99%
“…88 Schazmann et al reported on a solid-contact anion-SE based on the family of imidazolium salts covalently linked to PVC. 89 Here, the IL, with chloride as a counterion, served as an anion exchanger and a salt bridge, stabilizing the interfacial potential between the Ag/AgCl electrode substrate and the membrane. The resulting electrodes exhibited close to Nernstian slopes and stable and reproducible signals to different inorganic anions.…”
Section: ■ Sensor Materialsmentioning
confidence: 99%
“…Practitioners intending to apply ISEs in the field are typically critical of ISEs’ robustness and precision [ 11 ]. A significant amount of work has been done in recent years to address some of the common criticism [ 12 , 13 , 14 , 15 , 16 ]. Reducing the complexness of operation with ISEs with the view of reducing farmers’ distrust of analytical instrumentation is in a focus of our group.…”
Section: Introductionmentioning
confidence: 99%